(untitled) (Eurasian Journal of History, Geography and Economics, 2023)
Geographical study of agriculture, land and water resources and zoning problems are the methodological basis of any geographical research. In this respect, agrogeographical zoning is the territorial structure and specialization of agriculture. This article is devoted to the analysis of methods and stages of agricultural and land-water resources research.